2018
DOI: 10.4018/978-1-5225-3940-7.ch006
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Architecture for Adaptive, Intelligent, and Ubiquitous Educational Systems

Abstract: Ubiquitous learning environments (ULEs) allow real and virtual study materials to be combined to enrich learning experiences. Classrooms equipped with electronic devices produce artifacts that can reconstruct the captured experiences for later use and review. Those environments have the potential to turn themselves into a factory of learning objects (LOs), which may become useless if appropriate means for reaching them are not provided to students. On the other hand, adaptive educational hypermedia (AEH) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…To this end, our approach considers a hybrid student model that combines an ontology and a Bayesian network dedicated to identify students' knowledge based on their characteristics and behavior during the learning process, as described in Araújo et al (2018b).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…To this end, our approach considers a hybrid student model that combines an ontology and a Bayesian network dedicated to identify students' knowledge based on their characteristics and behavior during the learning process, as described in Araújo et al (2018b).…”
Section: Related Workmentioning
confidence: 99%
“…In addition, in this proposal a Ubiquitous Learning Environment (ULE), previously presented in Araújo et al (2017bAraújo et al ( , 2018b, records activities in an instrumented classroom, as shown in Fig. 1, with an electronic whiteboard, projectors, microphones and videocameras.…”
Section: Learning Objects Recommendation Architecture: An Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The relevance R for an LO o is given by Eq. (1), as the sum of values obtained by o in each of the eight LS [Araújo et al 2018].…”
Section: Content Personalizationmentioning
confidence: 99%